The Relationship of Peer Social Support to Anxiety Levels of Students in The Preparation of The Final Project of The Study Program Bachelor of Nursing at Mega Buana University Palopo in 2025 - Putri Dwiyani, Dea; Lindriani, Lindriani; Supri, Aisyah; Papayungan, Sutrisno (AACENDIKIA: Journal of Nursing, 2025)
Anxiety can arise, especially when students face difficulties, such as when they experience anxiety when compiling a final assignment. Students really need motivation and peer cooperation to solve problems that arise during the process of compiling a final assignment. To determine the relationship between social support, especially peers, and the level of anxiety of students in compiling a final assignment for the undergraduate nursing study program at Mega Buana University, Palopo. This study uses a quantitative, correlational design; variable testing uses Spearman's rho. The method applied in this study is cross-sectional, meaning that data are collected simultaneously for the independent and dependent variables. The results of the Spearman's rho statistical test using SPSS version 30 show that the ???? value (0.042) is a value that is smaller than α <0.05, which indicates acceptance of Ha and rejection of H0. Therefore, in compiling the final assignment for the Bachelor of Nursing Study Program at Mega Buana University, Palopo, there is a relationship between peer social support and students' anxiety levels. This is indicated by the correlation coefficient of 0.345, which is interpreted as a moderate, positive relationship. The results of the statistical test indicate that there is a relationship between peer social support and the level of student anxiety in compiling the final assignment of the undergraduate nursing study program at Mega Buana University, Palopo, in 2025, with a positive direction and a significant p-value.